Improving pre-roll advertisements through the use of congruence - Lee, Debbie Meiyi (2014)
Over the last decade, the field of advertising has expanded rapidly to include new formats such as online videos. The purpose of the current study is to investigate the effects of ad congruence (ad-context congruence and ad-profile congruence) on attitudes towards the ad and the brand in the new context of pre-roll advertisements. A total of 80 participants took part in a laboratory experiment where three pre-roll advertisements were paired with short videos. The results (n = 80) showed significant main effects of ad-context congruence on perceived irritation and attitude towards the ad. The results also showed significant main